Kinerja Keuangan dan Pertumbuhan Perusahaan Terhadap Kebijakan Dividen dengan Pengukuran Dividen Payout Ratio - Muhammad Rivandi; Putri Indriati (JURNAL PUNDI, 2022)
The purpose of investment done by investors in the capital market is to get return of said investment. Expectations of investors in investing is to obtain dividend payout ratio. dividend payout ratio can be determined by analyzing the company's financial performance which is proxied by Current Ratio, Return on Assets, and Company Growth. Dividend policy is an established guide for the firm to determine the amount of money it will pay out as dividends to investors. The size of the dividend to be distributed by the company to investors depends on the dividend policy of each company. This study aims to find out the effect of liquidity, profitability, and company’s growth on dividend policy. The sample of this research is LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020 which were selected using the purposive sampling method. The data analysis method used in this study is a panel data regression model. Based on the results of hypothesis testing, that liquidity has no effect on dividend policy, profitability has a significant negative effect on dividend policy, and company’s growth has no effect on dividend policy. Keywords: liquidity, profitability, company’s growth, dividend policy.